Evaluasi Pengendalian Penerapan Akuntansi Aset Tetap Pada Hotel Prama Sanur Beach Bali - I Gusti Ayu Nyoman Satriani; Sang Ayu Putu Arie Indraswarawati; Ni Made Wisni Arie Pramuki (UNHI Press, 2026)
This study aims to evaluate the implementation of fixed asset accounting based on PSAK 16 at the Prama Sanur Beach Hotel, Bali, specifically regarding the recognition, classification, and determination of the economic life of fixed assets. The research method used is descriptive qualitative with primary data sources obtained through observation, interviews, and documentation. The results of the study indicate that in general the company has implemented fixed asset recognition in accordance with PSAK 16, especially in the aspects of recognizing economic benefits and measuring acquisition costs. However, several obstacles are still found in practice, such as global asset recording without detailed classification by type, year of acquisition, and economic life. This causes difficulties in determining accurate depreciation and discrepancies between book values and the actual condition of assets in the field. In addition, limited documentation of old assets and lack of data updates also affect the quality of financial information. Therefore, a more structured and standardized evaluation and improvement of the fixed asset recording system is needed. This study is expected to contribute to improving the accuracy, transparency, and accountability of the company's financial statements, as well as serve as a reference for further research in the field of fixed asset accounting.